Hepatopulmonary Syndrome: A Brief Review - Amin Zulkifli; Amin Hilman Zulkifli; Tedyanto Nadim Marchian (Sciendo, 2016)
Hepatopulmonary syndrome (HPS) is a pulmonary complication of liver disease characterized by arterial hypoxemia. Mechanisms related to this event are diffusion-perfusion flaw, ventilation-perfusion (V/Q) mismatch, and direct arteriovenous shunts. Diagnosis of HPS is based on the presence of liver disease or portal hypertension, increased alveolar-arterial (A-a) PO2, and intrapulmonary vascular dilatations (IPVD). Lung transplantation (LT) remains the most effective therapy for HPS. In spite of its poor prognosis, we could improve the quality of life and survival rate of patients.